Analysis of Effects of Physical, Chemical and Biological Properties in Domestic Waste Water (Slugde) on Environmental Health in Abia State, Nigeria - C.A, Egbe; A. A., Dada (Universitas Terbuka, 2019)
The study analyze the physical, chemical and Biological properties of sludge (Domestic waste water) in Umuda-Isingwu, Umuahia-Ibeku and Ihie-ndume in Umuahia north local government area of Abia state. Simple random sampling technique was adopted for the study. Data obtained from laboratory analysis of the water samples was analyzed using descriptive and inferential statistical techniques notably mean, F-LSD and F -test. The mean values of the physical and chemical parameters were compared with SON’s and WHO’s permissible limits. In the chemical properties COD had a mean range of 69.03 ± 0.06 to 80.03 ± 0.06 with all the means showing significant difference among each other (P ? 0.05). The highest TSS was observed in Ibeku at 921.03 ± 0.06. Nickel had a range of 7.42 ± 0.01 to 8.71 ± 0.01 Mg/l with all the means showing significant difference (P ? 0.05). PO4 had its highest concentration in Ihie Ndume community with a mean of 54.03 ± 0.06 Mg/l. None of the means of pH was seen to be above the WHO permissible limit of 8.5, as the mean range of pH was between 6.11 ± 0.01 to 7.76 ± 0.01. The E. coli load was high at Umuda Isingwu, followed by Ibeku and then Ihie Ndume. P. aeruginos and S. aereus was not observed in Ihie Ndume. The presence of fecal coliform bacteria is an indicator that a potential health hazard exists for individuals exposed to the source of water. Nickel was found to be slightly elevated at most of the sites above WHO. Trace metals have been implicated to be responsible for certain health disorders. The PO43- levels varied along the sampling community sites with some sites values having relatively higher values. In general the quality of these waste water cannot be guaranteed as most of the indicators were higher than the WHO and SON standards. This paper assumes that waste water evaluated pose huge treat to the immediate environment and should be investigated further in addition to epidemiological evaluation of the community to rule out occurrence of water-borne diseases.